The Use of Lexical Hedges by the Main Character in the Film Eighth Grade (2018) (Cinematology: Journal Anthology of Film and Television Studies, 2026)
This study discusses the use of lexical hedges in the main character’s utterances in the film Eighth Grade (2018). This is shown by the frequent uses of lexical hedges by the main character, who has social anxiety and an introverted personality. The purpose of this study is to analyze the types and functions of lexical hedges used by the main character in the film. This study applies Namsaraev’s (2010) theory to analyze the types of lexical hedges and Coates’ (2013) theory to identify their functions. This research adopts a descriptive qualitative approach. The results show that there are 42 data that can be categorized into four types of lexical hedges, which are modal auxiliary verbs, lexical verbs, adverbs, and fillers. Among these, fillers are the most frequently used type by the main character. In addition, the main character uses hedges to express uncertainty and to search for the right words. Based on the analysis, the most dominant function of hedges is to search for the right words. This study concludes that the use of lexical hedges can be influenced by an individual’s social identity.